The regulation of cognitive enhancement devices: refining Maslen et al.'s model - Maslen, H; Douglas, T; Kadosh, R; Levy, N; Savulescu, J (Oxford University Press, 2015)
Our (2014) model for the regulation of cognitive enhancement devices (CEDs) received a great deal of interest from those involved in European device regulation and from academic commentators. Further, since the publication of our recommendations, the number of manufacturers of brain stimulation devices for non-medical purposes has increased, underscoring the need for a regulatory response. In this paper, we clarify aspects of our original proposal and address additional regulatory issues beyond our original focus on the sale of devices. We begin with theoretical points pertaining to the definition of a CED and the distinction between treatment and enhancement. We then respond to practical challenges raised by the prospect of implementing our regulatory framework. Next, we address some wider societal considerations relating to users and other stakeholders. Finally, we revisit the broader regulatory context within which the various discussions are situated.